Comparing Zinc Finger Nucleases and Transcription Activator-Like Effector Nucleases for Gene Targeting in Drosophila - Beumer, Kelly J. (Genetics Society of America, 2013)
Zinc-finger nucleases have proven to be successful as reagents for targeted genome manipulation in Drosophila melanogaster and many other organisms. Their utility has been limited, however, by the significant failure rate of new designs, reflecting the complexity of DNA recognition by zinc fingers. Transcription activator-like effector (TALE) DNA-binding domains depend on a simple, one-module-to-one-base-pair recognition code, and they have been very productively incorporated into nucleases (TALENs) for genome engineering. In this report we describe the design of TALENs for a number of different genes in Drosophila, and we explore several parameters of TALEN design. The rate of success with TALENs was substantially greater than for zinc-finger nucleases , and the frequency of mutagenesis was comparable. Knockout mutations were isolated in several genes in which such alleles were not previously available. TALENs are an effective tool for targeted genome manipulation in Drosophila.